DEMOCRATIC PROGRESSIVE PARTY’S DIGITAL POPULISM TOWARDS REUNIFICATION NARRATIVES IN X 2020-2024 - Yanuariandi, Muhamad Alfi; Jatmika, Sidik (Sosiohumaniora, 2025)
This research aims to analyze how the Democratic Progressive Party (DPP) utilizes digital populism on platform X (formerly Twitter) to reinforce Taiwan's distinct identity and shape public opinion regarding Taiwan-China reunification. A mixed-methods approach was employed, analyzing 920 posts from 2020 to 2024. Data were examined using Naïve Bayes classification for quantitative sentiment analysis and qualitative thematic evaluation grounded in Social Identity Theory. The research results reveal three primary findings. First, the DPP successfully establishes an "in-group" identity based on progressive and democratic ideals, contrasted with an "out-group" depiction of Chinese authoritarianism. Second, although the DPP effectively controls digital discourse on sovereignty and social initiatives, sentiment analysis indicates persistent polarization in public responses. Third, while "inclusive populism" has effectively fostered group preference and political allegiance, this approach encounters constraints associated with fundamental geopolitical issues. These discoveries highlight that digital populism serves as an effective tool for identity consolidation, though it may intensify societal divisions rather than establishing a broad consensus in cross-strait interactions. This research explores the role of social media within East Asian security dynamics and examines the influence of digital communication on regional political stability.